Break-ar a vida: processos de subjetivação de jovens negros por meio da dança na cidade de São Paulo - Santos, Wanderley Moreira dos (2009)
His research is the mapping of break in the city of São Paulo, a dance that appeared in the decade of 70 in the United States from the present tension in the classroom and race relations and that it makes with that the Puerto Ricans and blacks they created a dance style in which was possible to bring for visible and the audible one what it was in the order of the sensation. Before being a dance, break is the instrumental band of funk in which the strokes and the lines of low are valued. The differentiated form for which, boys and girls they danced in this part of funk. They and they had passed to be identified as b.boys and b.girls, name given for DJ Kool Herc, one of the jamaicanos, that immigrated for the United States in the decade of 60, and produced the Block Partie, (block parties), packed for soul, funk, jazz and Latin musics in the quarter of the Bronx, in New York. Next to the sprouting of break, a new rhythm musical, proceeding from the junction of samples of rhythms of hip-hop, funk and the electrum is created, break beat. This hybrid music was created by the proper Kool Herc, and has multiple variations. This modality of dance was connected to the movement hip-hop and in it gained form. In this cartography song had the necessity of minimum perscrutar the passages of the configuration of protest, movement initiated in the United States, but that it left its tracks in some black diásporas, in special in Brazil. It is not, however, an attempt of return to the archaic one, and yes, to trace tenuous lines of what I called, provisorily, of magnifying of the militancy, which can suggestively be defined as fusing of the music and the militancy that creates a powerful mesh-ardilosa in the invocation of the bodies, the subjectivity and the life, especially of the black population